Research and application of key technologies for data delivery in railway engineering design based on metadata - Xiangru Lyu; Xunxiao Yin; Kun Wang; Yongwen Wei (High-Speed Railway)
In view of the problems of inconsistent data semantics, inconsistent data formats, and difficult data quality assurance between the railway engineering design phase and the construction and operation phase, as well as the difficulty in fully realizing the value of design results, this paper proposes a design and implementation scheme for a railway engineering collaborative design platform. The railway engineering collaborative design platform mainly includes functional modules such as metadata management, design collaboration, design delivery management, model component library, model rendering services, and Building Information Modeling (BIM) application services. Based on this, research is conducted on multi-disciplinary parameterized collaborative design technology for railway engineering, infrastructure data management and delivery technology, and design multi-source data fusion and application technology. The railway engineering collaborative design platform is compared with other railway design software to further validate its advantages and advanced features. The platform has been widely applied in multiple railway construction projects, greatly improving the design and project management efficiency.